PENGGUNAAN ANTIBIOTIK PADA PASIEN BPJS DI IGD RSUD dr. GONDO SUWARNO KABUPATEN SEMARANG - Rias Ayu Kartika; Maria Caecilia Nanny Setiawati; Erna Prasetyaningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2022)
The antibiotics used for patients in the ER (emergency room) needs special attention, because the inappropriate use of antibiotics at the beginning of treatment can affect subsequent antibiotic therapy. This study intents to evaluate antibiotics used in BPJS patients in the emergency department of RSUD dr. Gondo Suwarno, Semarang Regency. This research was conducted using prescription data for BPJS patients at the ER at RSUD dr. Gondo Suwarno, Semarang Regency for the period January-June 2020. We used purposive sampling as a technic sampling and the data is collective retrospectively. The results showed that 30.64% of the total prescriptions for antibiotics were prescribed for 478 patients, most of whom were adult patients (26-45 years), which were 29.71%. Most route of administration is per oral (76.09%). Diagnosis of antibiotics, the most are trauma and open wounds (40.38%). 75.94% of antibiotics were given singly, most in order were ciprofloxacin (17.36%), amoxicillin (15.9%) and cefixime (13.81%) all orally. The most common combination antibiotics were oral amoxicillin and topical gentamicin (14.44%). All antibiotics prescribed were in accordance with the national formulary. According to the WHO criteria, the total drug prescribed per sheet and the percentage of antibiotic prescriptions for BPJS patients in the emergency room of RSUD dr. Gondo Suwarno, Semarang Regency, has not been rational, while the percentage of injection prescriptions, generic antibiotic prescriptions and conformity with National Formulary is rational.